Sorvete próbiotico de guabijú (myrcianthes pungens): desenvolvimento, caracterização, avaliação de compostos bioativos e viabilidade de lactobacillus paracasei - Detoni, Elisandra (2020)
Ice cream is a dairy product, composed of sugar, emulsifiers, stabilizers and flavorings. A functional ice cream with healthier characteristics can be produced by adding bioactive compounds like probiotics and natural antioxidants. Probiotics are living microorganisms that confer benefits to the health of the host and can characterize the products as functional. Antioxidants are compounds that effectively inhibit the oxidation of a substrate and are present in numerous plants. Some native fruits are little known, but the consumption of their fruits can bring health benefits. Guabijú (Myrcianthes pungens) is a fruit native to Brazil, characterized by its pleasant sweet flavor and purple color when ripe. The use of fruits of native species in food products is evidenced in the literature due to the presence of bioactive compounds and different sensory properties. Thus, an ice cream was developed, with the addition of freeze-dried guabijú flour and the probiotic microorganism Lactobacillus paracasei, aiming at a product with functional properties. The fresh fruits were collected in two periods, December 2018 and January 2019 in different plants. The fruits were evaluated for physical-chemical composition, total anthocyanin, phenolic compounds and antioxidant activity, together with the developed flours. The ice cream was developed using three different concentrations of flour, 4%, 8% and 12% and was analyzed for physical-chemical, bioactive, microbiological and sensory composition. During a 90-day storage period, the probiotic viability of the added microorganism was analyzed by counting lactic acid bacteria. The fresh fruit and the flour obtained from the December and January harvest showed antioxidant activity, presence of anthocyanins and phenolic compounds and the use of freeze drying concentrated the contents of these bioactive compounds (anthocyanins between 201 and 220 mg 100 g-1, 1822 phenolic compounds at 1919 mg EAG 100 g-1), maintaining antioxidant activity (39 to 60 g g-1 DPPH). January flour obtained greater acidity, higher sugar content, more intense purple color and greater antioxidant activity being added to the ice cream. This resulted in ice cream with nutritional characteristics, presence of anthocyanins (7.41 to 11.41 mg 100 g-1), phenolic compounds (215 to 317 mg EAG 100 g-1), antioxidant activity (EC50 1829 to 472 g g-1 DPPH), with proven microbiological quality and potential for the vehicle of the probiotic Lactobacillus paracasei. In the sensory acceptance, the addition of up to 8% of guabijú flour to the ice cream was accepted by consumers with acceptability indexes> 78% for the evaluated attributes and purchase intention in the “certainly would buy” degree.